An Amphiphilic Ruthenium Polymetallodrug for Combined Photodynamic Therapy and Photochemotherapy In Vivo. Issue 6 (5th December 2016) - Sun, Wen; Li, Shuyi; Häupler, Bernhard; Liu, Juan; Jin, Shubin; Steffen, Werner; Schubert, Ulrich S.; Butt, Hans‐Jürgen; Liang, Xing‐Jie; Wu, Si
Abstract : An amphiphilic Ru‐containing block copolymer is used as a photoactivated polymetallodrug for anticancer phototherapy. The block copolymer self‐assembles into nanoparticles, which can accumulate at tumor sites in a mouse model. Red light irradiation of the block copolymer nanoparticles releases anticancer Ru complexes and generates cytotoxic 1 O2, both of which can inhibit tumor growth.